(8a-7)(4a-3)=0

Simple and best practice solution for (8a-7)(4a-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8a-7)(4a-3)=0 equation:


Simplifying
(8a + -7)(4a + -3) = 0

Reorder the terms:
(-7 + 8a)(4a + -3) = 0

Reorder the terms:
(-7 + 8a)(-3 + 4a) = 0

Multiply (-7 + 8a) * (-3 + 4a)
(-7(-3 + 4a) + 8a * (-3 + 4a)) = 0
((-3 * -7 + 4a * -7) + 8a * (-3 + 4a)) = 0
((21 + -28a) + 8a * (-3 + 4a)) = 0
(21 + -28a + (-3 * 8a + 4a * 8a)) = 0
(21 + -28a + (-24a + 32a2)) = 0

Combine like terms: -28a + -24a = -52a
(21 + -52a + 32a2) = 0

Solving
21 + -52a + 32a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(3 + -4a)(7 + -8a) = 0

Subproblem 1

Set the factor '(3 + -4a)' equal to zero and attempt to solve: Simplifying 3 + -4a = 0 Solving 3 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4a = 0 + -3 -4a = 0 + -3 Combine like terms: 0 + -3 = -3 -4a = -3 Divide each side by '-4'. a = 0.75 Simplifying a = 0.75

Subproblem 2

Set the factor '(7 + -8a)' equal to zero and attempt to solve: Simplifying 7 + -8a = 0 Solving 7 + -8a = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -8a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -8a = 0 + -7 -8a = 0 + -7 Combine like terms: 0 + -7 = -7 -8a = -7 Divide each side by '-8'. a = 0.875 Simplifying a = 0.875

Solution

a = {0.75, 0.875}

See similar equations:

| 3x^2+4x-5-7x^2-4x+8= | | 12(3x-9)=3(12x+5) | | In(x)=7 | | 42=6t | | 2x-8=x+7 | | Ln(4x-5)=0 | | 157.78=2.41w+14.23 | | -421=7(-4+7n)-1 | | Y=-3x-12+5 | | 12x+3=8x+7 | | -8p+9+9p=15 | | x^2+14x=900 | | 135+5=140-40 | | 0=x^2-14x+45 | | 5(2a-5b+3c)= | | d^2+12d+36= | | 7x-5=3x+10 | | -3-(-3x)=0 | | 3x+5=4x-40 | | -4-(-3x)=0 | | -2-(-3x)=0 | | 4w^2-28=0 | | y+12y=8 | | 0.2X+27=82 | | -1-(-3x)=0 | | -4(3x+3)=-4(5x-3) | | x+mx+b=0 | | 0=x^2+11x+18 | | 7x+12=0 | | 7c+3=13 | | 0=x^2-11x+18 | | 10x=6x-12 |

Equations solver categories